Investigating design principles for lecturers using Learning Management System data in large first-year university courses - Mlungu, Fezile Cecil (Rhodes University, 2026)
This study investigates how lecturers at a rural-based, comprehensive South African university can be supported in utilising Learning Management System (LMS) course data to make timely, context-sensitive decisions that support students in large first-year, first-semester courses. Using a single-iteration Design-Based Research (DBR) approach, the study responds to the limited use of course-level learning analytics (LA) in South African higher education and the challenges lecturers face in interpreting LMS course data for pedagogical decision-making. The design of the intervention draws on Marsh’s (2012) Theory of Action for Data Use and an adapted Data Information Knowledge Wisdom (DIKW) framework, extended to DIKWA by adding the Action level. The study refined six draft design principles into 11 that can inform e-learning specialists in supporting lecturers through a structured, course-data-informed decision-making process that moves from raw data to actionable insights. The intervention was co-designed with six lecturers teaching five large classes, each with approximately 300–1,400 students across all courses, and implemented through workshop, individual discussions, and follow-up consultations. In this study, the DIKWA framework was used not only to inform the intervention but also to guide lecturers in course-data-informed decision-making and student support. Their experiences were captured through data storytelling, revealing how course data-informed insights shaped their approaches to student support. Findings show that the intervention enhanced lecturers’ data literacies, enabling them to move beyond using the LMS merely for content distribution and formal assessments. However, the intervention also uncovered critical contextual barriers. Across the majority of lecturers, limited and unreliable Internet connectivity, particularly for students living in off-campus residences, was found to be the primary cause of low access to resources and low completion rates of activities, rather than a lack of motivation, as lecturers and researchers initially believed. Lecturers’ time constraints further influenced their capacity to complete the full DIKWA cycle. The study concludes that DIKWA-led student support, grounded in a course-data-informed decision-making process and combined with human-centred pedagogical considerations, is achievable and valuable in rural-based universities when supported as per the intervention.
Keywords: Education (Higher) -- South Africa (http://id.loc.gov/authorities/subjects/sh99005764); Design-based research (https://www.wikidata.org/wiki/Q5264236); Learning analytics (https://www.wikidata.org/wiki/Q2845208); Data literacy (https://www.wikidata.org/wiki/Q17067559)